Micturitional disturbance in patients with Guillain-Barré syndrome - Sakakibara, R. (BMJ Group, 1997)
OBJECTIVES—To examine the frequency and pathophysiology of micturitional disturbance in patients with Guillain-Barré syndrome. METHODS—Micturitional symptoms were noted and neurological examinations made repeatedly during admission to hospital of patients with clinical and neurophysiologically definite Guillain-Barré syndrome. Urodynamic studies consisted of uroflowmetry, measurement of residual urine, urethral pressure profilometry, medium fill water cystometry, and external sphincter EMG. RESULTS—Seven of 28 (25%) patients with Guillain-Barré syndrome showed micturitional disturbance. The symptoms included voiding difficulty in six, urinary retention in three, nocturnal urinary frequency in three, and urge incontinence in two. These micturitional symptoms appeared after weakness occurred, and improved gradually along with the neurological signs. All three patients who showed retention became able to urinate. Urodynamic studies were made on four symptomatic patients two of whom underwent repeated study. Disturbed bladder sensation was noted in one patient, bladder areflexia in one, and absence of the bulbocavernosus reflex in one. Cystometry showed decreased bladder volume in two and bladder overactivity in two, one of whom had urge urinary incontinence and the other urinary retention. CONCLUSIONS—A quarter of the patients with Guillain-Barré syndrome tend to have micturitional disturbance. The patients studied had evacuation and storage disorders, as well as bladder areflexia and disturbed bladder sensation indicative of peripheral types of parasympathetic and somatic nerve dysfunction. Decreased bladder volume with bladder overactivity but no evidence of CNS involvement was also found, evidence that bladder overactivity also occurs in peripheral nerve lesions with probable pelvic nerve irritation.